The effect of human papillomavirus status on prognosis and local treatment strategies of T1-2N0 oropharyngeal squamous cell cancer - Zhou, Ping; Chen, Deng-Lin; Lian, Chen-Lu; Wu, San-Gang; Zhang, Shi-Yang (Frontiers in Public Health, 2022)
Purpose: To explore the effect of human papillomavirus (HPV) status on prognosis and further investigate whether human papillomavirus (HPV) status has an impact on the local treatment strategies for T1-2N0 oropharyngeal squamous cell cancer (OPSCC) patients. Methods: Patients diagnosed with T1-2N0 OPSCC between 2010 and 2015 were included from the Surveillance, Epidemiology, and End Results database. Data were analyzed using propensity score matching (PSM), Chi-square test, Kaplan-Meier survival analysis, and Cox multivariable analyses. Results: A total of 1004 patients were identified, of whom 595 (59.3%) had HPV-related tumors. Of all the patients, 386 (38.4%) and 618 (61.6%) received definitive radiotherapy and radical surgery, respectively. HPV status had no significant effect on local treatment strategies for early-stage OPSCC (P=0.817). The 9-year cancer-specific survival (CSS) and overall survival (OS) were 89.6% and 80.1%, respectively. Compared to those with HPV-negative diseases, patients with HPV-positive diseases had better CSS and OS. A total of 222 pairs of patients were completely matched after PSM. The results of multivariate Cox regression analysis showed that patients with HPV-positive disease had significantly better CSS (P=0.001) and OS (P<0.001) compared to those with HPV-negative tumors. However, local treatment strategy was not associated with survival outcomes after PSM (CSS, P=0.440; OS, P=0.771). The subgroup analysis showed comparable CSS (P=0.576) and OS (P=0.932) between those treated with radical surgery and definitive radiotherapy regardless of HPV status. Conclusions: HPV status is an independent prognostic factor for the survival of stage T1-2N0 OPSCC patients. Local treatment strategies had no significant effect on the survival of early-stage OPSCC regardless of HPV status. Patients with early-stage OPSCC should be informed regarding the pros and cons of definitive radiotherapy or radical surgery.